Indonesia's Struggle: Jemaah Islamiyah and the Soul of Islam (Conversations in religion and theology, 2006)
Indonesia's Struggle: Jemaah Islamiyah and the Soul of Islam, Greg Barton Reviewed by Ian S. Markham Hartford Seminary, USA Response to Ian S. Markham By Greg Barton Asia–Pacific Center for Security Studies in Honolulu, Hawaii, USA